Flowering of Zizуphus jujubа Mill. in Kherson region (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
A comparative characteristics of flowering time of 15 cultivars and forms of Zizuphus jujuba grown in Kherson region are given. The numbers of the effective temperatures (> 10 º C) at the beginning and at the end of flowering time are presented.
Keywords: Zizyphus jujuba, cultivars, flowering, Kherson region.